2010
DOI: 10.1007/s00417-010-1573-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of advanced glycation end products, oxidative stress and nuclear factor-kappaB in the development of diabetic keratopathy

Abstract: The higher expression of AGE, 8-OHdG and NF-κB in corneal tissues of diabetic rats suggests that these factors are involved in apoptosis and in subsequent corneal alterations related to diabetic keratopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 39 publications
3
63
0
1
Order By: Relevance
“…These findings confirmed the high concentrations of the AGEs in corneal endothelium, and they suggested that the high expression of the AGEs in the iris and the aqueous humor may directly affect the corneal endothelium, subsequently leading to increased AGE expression [26]. The level of fluorescence is higher in diabetic corneas than in normal corneas because of the due AGEs [15]. Moreover, treatment with aminoguanidine, an AGEs inhibitor, prevented diabetic corneal structural abnormalities, such as the degeneration of intracellular organelles, cytoplasmic vacuole formation, and edema in the corneal stroma [27].…”
Section: Pathophysiology Of Diabetic Keratopa-thysupporting
confidence: 83%
See 2 more Smart Citations
“…These findings confirmed the high concentrations of the AGEs in corneal endothelium, and they suggested that the high expression of the AGEs in the iris and the aqueous humor may directly affect the corneal endothelium, subsequently leading to increased AGE expression [26]. The level of fluorescence is higher in diabetic corneas than in normal corneas because of the due AGEs [15]. Moreover, treatment with aminoguanidine, an AGEs inhibitor, prevented diabetic corneal structural abnormalities, such as the degeneration of intracellular organelles, cytoplasmic vacuole formation, and edema in the corneal stroma [27].…”
Section: Pathophysiology Of Diabetic Keratopa-thysupporting
confidence: 83%
“…The increased accumulation of the AGEs in diabetic corneas provided strong evidence that nuclear oxidative DNA damage caused by the accumulation of the AGEs is responsible for the apoptotic damage of corneal cells in diabetic patients ( Fig. 1) [15].…”
Section: Pathophysiology Of Diabetic Keratopa-thymentioning
confidence: 98%
See 1 more Smart Citation
“…Importantly, the diabetic corneal stroma accumulates AGEs, which may lead to collagen crosslinking and could contribute to increased central corneal thickness (Sady et al, 1995). This accumulation may also underlie changes in type IV collagen expression, impaired cell adhesion, and increased keratocyte apoptosis observed in mice with NIDDM and in rats with IDDM (Watanabe et al, 2002; Kim et al, 2011). In diabetic rats, stromal edema was also reported (Gül et al, 2008).…”
Section: General Manifestations Of Diabetes In the Corneamentioning
confidence: 99%
“…AGEs interact with their receptors (RAGEs) triggering intracellular signaling including NF-κB activation and formation of reactive oxygen species (ROS) (Kim et al, 2011; Shi et al, 2013a;b). Their accumulation in the diabetic corneal BMs and stroma may be responsible for clinically observed increased autofluorescence (Kaji et al, 2000; McDermott et al, 2003; Calvo-Maroto et al, 2016).…”
Section: Molecular Alterations and Disease Markers Of Diabetes In mentioning
confidence: 99%